Design of a modified natural egyptian solar house - Hanaa M. Farghally; Faten H. Fahmy; Amal A. Hassan; Ninet M. Ahmed (Institute of Advanced Engineering and Science, 2020)
The rate of increase in energy consumption and high costs in addition to the depletion of existing resources has a significant impact on our standard of living for next generations. In this case, the priority is to develop alternative cost-effective sources for powering the residential and non-residential buildings. This paper proposes and develops a design of a modified small two-story residential solar house for a medium-sized family located in Cairo, Egypt. This modified solar house meets almost all its energy demands including space heating by using solar air collector with a pebble storage unit in winter and a summer cooling system using wind catcher theory. Hot water is obtained throughout the day by using a steel sheltered water storage tank with a capacity of 1000 liter. Finally, the proposed heating system of the solar house is sized and modeled.